Adapting Existing Hospitals for Infectious Disease Prevention and Control - A. S. A. S. Elsaadany; Khaled Ahmed (Journal of Engineering Research - Egypt, 2022)
Currently, there isa deficit efficient and contextualized design strategies to aid in infection prevention and save health professionals. Thus, the paper's objective is to validate how the room we enthrall can be made safer from the perspective of architectural design with the aim of creating rules for politicians and highlighting the role of the architect in battling diseases. Two hospitals have been considered to apply these conditions to adapt with new polices of infection control. The modifications have revealed good results that the hospitals have been divided into three sections, triaging, isolated patients, and normal patients.